Maturity and spawning habits of Nemipterus japonicus (Bloch) off Visakhapatnam* - Rao, D Manikyala; Rao, K Srinivasa (Indian Journal of Fisheries, 2011)
The Japanese threadfin bream, Nemipterus japonicus (Bloch) forms an important fishery (approx. 13%) among the demersal catches landing at Visakhapatnam (Rao 1981). Earlier studies on N. japonicus include its biology (Kuthalingam 1965, Krishnamoorthi 1971, Eggleston 1972, Murty 1984) and maturity stages and fecundity (Dan 1977). Various aspects of maturity and spawning of this species were studied and are presented here.